2021
DOI: 10.18517/ijaseit.11.3.12343
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stage in Designing Household Constructed Wetlands: Selection of a Suitable Aquatic Plant

Abstract: Constructing centralized wastewater treatment plant systems to serve and control city sanitation requirements is vastly expensive in developing countries. Consequently, employing decentralized wastewater treatment systems through utilizing constructed wetlands (CWs) for individual households should be promoted. In this study, the most appropriate aquatic species planted in constructed wetlands were examined for treating greywater at the household level in humid tropical regions. Three different decorative aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…There are numerous aquatic plant species, but it was recommended that locally available aquatic plant species need to be chosen [7,14]. A previous study found that among the existing plants in the study area, Cyperus alternifolius was the most suitable for use in CWs for greywater treatment in tropical areas [21]. Because of that, the Cyperus alternifolius is used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous aquatic plant species, but it was recommended that locally available aquatic plant species need to be chosen [7,14]. A previous study found that among the existing plants in the study area, Cyperus alternifolius was the most suitable for use in CWs for greywater treatment in tropical areas [21]. Because of that, the Cyperus alternifolius is used in this study.…”
Section: Introductionmentioning
confidence: 99%